A alteridade em “carne e osso”: uma perspectiva levinasiana de Vidas Secas - Gomes, Camila Pacheco (2020)
This dissertation thematizes one of the main categories of Emmanuel Levinas' (1906-1995) thought, namely, the phenomenon of alterity, having as a background the novel Vidas Secas (1938) by Graciliano Ramos (1892-1953). For this, inspired in the levinasian work Totality and Infinity (1961), the paper pursues to reconstitute the critique to the Cartesian rationalism and, in passing, to the husserlian phenomenological idealism through a resumption and deepening of the notions of subjectivity and intersubjectivity. This moment is articulated through two important records of the philosophical tradition in the West: one of them instituted by the Cartesian principle of the cogito as the ultimate foundation of which the presence of another is devoid of any more decisive ontological brio; and the second record is the husserlian theory which, while recognizing the phenomenon of Other, does not abdicate the same principle idealism. The second moment of the research deals more directly with the meaning and scope of the category of alterity within Levinas' reflection as the place, par excellence, of transcendence. It is therefore a matter of understanding the philosopher's critique to the category of totality in order to think Outro as Outrem through the ethico-phenomenological horizon of carnality. This aspect will be better illustrated in the third moment of the text from a convergence with the literature, especially Vidas Secas. The greater interest in this approach is due to the fact that, in the midst of the arid scenario, the gracilian characters reveal themselves "in flesh and blood", that is, in their too human condition, which confers a singular status of radical alterity. Finally, the work advocates the thesis that the work of Graciliano, so well portrayed in the series titled Os Retirantes (1944) by Portinari (1903-1962), problematizes the ideal of philosophical solipsism proposed by Husserl and radicalized, to the last consequences, by Levinas.